On lower bounds for the approximation of functions by local splines with nonfixed nodes - Shumeiko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For functions integrable to the power \(β = (r + 1 + 1/p)^{ - 1} \) , we obtain asymptotically exact lower bounds for the approximation by local splines of degree r and defect k< r/2 in the metric of L p